Enhanced photocatalytic activity of novel TiO2/Ag/MoS2/Ag nanocomposites for water-treatment. Issue 4 (March 2020) - Jiang, Nan; Du, Yi; Ji, Peihong; Liu, Shiquan; He, Bo; Qu, Junnan; Wang, Jiajia; Sun, Xinyue; Liu, Yang; Li, Haoyu
Abstract: MoS2 /TiO2 based nanocomposites exhibit great prospect in the area of photocatalysis and rechargeable batteries. However, many efforts have to be made to avoid the agglomeration of MoS2 on TiO2 nanobelts, to increase the interfacial bonding between MoS2 and TiO2, and to utilize the inert basal surface of 2H–MoS2 . Herein, we report the TiO2 /Ag/MoS2 /Ag nanocomposites with double Ag loadings by hydrothermal method combined with the Tollen reaction. The as-obtained nanocomposites possess excellent photocatalytic performance to Cr (Ⅵ) and RhB, which is ascribed to the fast transfer and effective separation of charge carriers due to the formation of heterojunction between TiO2 /Ag/MoS2 and MoS2 /Ag. The present study illustrates the potential application of these analogous multiphase nanocomposites for water purification.